2020
DOI: 10.1016/j.mehy.2020.110214
|View full text |Cite
|
Sign up to set email alerts
|

Role of latent tuberculosis infections in reduced COVID-19 mortality: Evidence from an instrumental variable method analysis

Abstract: Since the outbreak of the coronavirus disease 2019 (COVID-19) pandemic, there has been significant interest in the potential protective effect of the Bacillus Calmette-Guerin (BCG) vaccine against COVID-19 mortality. This effect has been attributed to innate immune responses induced by BCG vaccination. However, these studies ignore an important fact: according to World Health Organization estimates, about a quarter of the world's population may have latent tuberculosis infection (LTBI), a condition in which th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 6 publications
1
22
0
Order By: Relevance
“…In this study the prevalence of mycobacterium spp. (standardized to BCG vaccine coverae) exposure of the populations is negatively associated with COVID-19 deaths per million populations, this supports the previous mentioned studies 25,26, 27,28…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study the prevalence of mycobacterium spp. (standardized to BCG vaccine coverae) exposure of the populations is negatively associated with COVID-19 deaths per million populations, this supports the previous mentioned studies 25,26, 27,28…”
Section: Discussionsupporting
confidence: 89%
“…However, the scenario in high prevalence countries like many countries in Asia and Africa is quite the opposite, where reinfection due to contact with active cases rather than reactivation contributes to a high disease burden 24 . Latent TB infections was suggested to create heterogeneous immune response to COX-COV2 viral infection in different patterns and severity according to different BCG status 25 further studies consolidate such latent TB role thereafter 26,27,28 .…”
Section: Introductionmentioning
confidence: 89%
“…Few studies are investigating the relationship between LTBI and COVID-19 with this hypothesis. In the study of Takahashi [ 1 ], it was shown that LTBI was associated with a decrease in the COVID-19 mortality rate. In our study, no difference was found between the TBF test-positive group and the TBF test-negative group regarding the frequency of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID-19), an infectious disease caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus, affected the whole world after the first case was reported in Wuhan, China, in December 2019 [ 1 ]. While the COVID-19 pandemic continues its impact with high mortality and morbidity, the search to reduce these effects continues.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, cross immune heterogenecity was suggested between BCG and certain viral diseases since BCG induces trained immunity through expressing heterologous antigens of different pathogens which have been developed and tested since 1991 30 . Different studies have already show statistical associations of BCG vaccinations and TB prevalence status with reduced severity of COVID-19 disease 31,32,33,34, 35 . These studies suggest that BCG and natural latent TB infection induce heterogeneous immunity against SARS-CoV2.…”
Section: Introductionmentioning
confidence: 98%